Hearts on the agenda / Fifty Years of the First Heart Transplantation in Brazil: Dr. Zerbini Put the Brazilian Cardiac Surgery in the Map! / 50 Years of Cardiac Transplantation ... a medical journey of courage, dedication and innovation - Sergio Eduardo de Paiva Gonçalves; José Benedito Oliveira Amorim; Ema Ely Salomão Bonetti (Brazilian Dental Science)
Hearts on the agendaSymbol of affection and keeper of the deepest emotions of human beings, the heart is the agenda of BDS editorials of this issue.Two major Brazilian events, in two completely different sectors of knowledge, place side by side the deepest nationalist emotions: on the one hand, the heart transplant surgery that this year marks 50 years of its first realization in Brazil by Dr. Zerbini and team (Editorial written by the Physiologist Jose Benedito de Oliveira Amorim); on the other, the first Brazilian Rhapsody, composed by a woman (Zélia Marão), commissioned by a medical coordinator of an Environmental Preservation Center-CAEB (Dr. Ema Ely Salomão Bonetti), in whose libretto we extracted the fantastic cover image of this issue. Dr. Ema tells us in her editorial the worldwide position regarding heart transplants and provides us with the cover image of this issue.Science, health, art and emotion in an incentive to preserve the quality of life.